236 PREDICTORS OF ADVERSE OUTCOMES IN OLDER PATIENTS DISCHARGED DIRECTLY FROM THE EMERGENCY DEPARTMENT. (18th November 2021) - Mohamed, A; Gabr, A; Cassarino, M; Leahy, A; Ali, B; Okpaje, B; Saleh, A; Mannion, M; Carroll, I; Hayes, C; Peters, C; Shanahan, E; et al.
Abstract: Background: Over 40% of older patients are discharged directly from the Emergency Department (ED) and this cohort is at increased risk of adverse outcomes. The purpose of this study was to explore the factors that predict future adverse outcomes in this cohort to inform practice, resource planning and policy. Methods: A secondary analysis of the OPTIMEND, a single-centre, randomized-controlled trial was completed. OPTIMEND examined the effectiveness of an intervention by a team of Health and Social Care Professionals along with usual care and compared this to standard ED care alone (Dec 2018-May 2019). The inclusion criteria were adults aged 65 years and over presenting to the ED at a University Teaching Hospital with medical complaints and a Manchester Triage System category 2–5. Results: 220 patients were included (median age 79 years; 62% female). Median length of stay in ED was 5.5 hrs. 70 patients re-attended the ED within 6 months with 43 re-hospitalised within 6 months. 9 patients died within six months of discharge. Multivariant logistic regression was completed. Age was the only independent predictor of mortality within six months of discharge {Odds Ratio (OR) 1.15, p = 0.044}. Past hospitalisation (<6 months) was associated with a lower likelihood of ED re-attendance, and rehospitalization within six months of discharge (OR: 0.452 p = 0.022; OR:0.442, p = 0.046; respectively). Clinical Frailty Score was associated with a significantly higher likelihood of rehospitalization (OR:1.48, p = 0.031) but not with ED revisits (OR: 1.235, p = 0.165). Conclusion: Older people have a high ED re-attendance rate of 33% after an index visit with 20% hospitalized subsequently. Frailty is a significant predictor of rehospitalisation. Rapid and targeted intervention for frail patients who reattend the ED should be a priority for the integrated care program to enhance admission avoidance.